A Study on the Mechanisms of Christian Universities’ Compliance with the Nationalist Government’s Party-Oriented Education Policy: Focusing on Jinling University - ZHAO Feifei (Journal of Research for Christianity in China (JRCC), 2025)
After the establishment of the Nanjing Nationalist Government, the implementation of Party-oriented education across all levels of schools presented new challenges to Christian universities founded in China by Western nations since modern times. However, most Christian universities adapted to this policy to varying degrees, securing legitimacy under the new circumstances. What were the reasons behind this? Examined from the perspective of political-cultural mechanisms, there existed areas for communication and coordination between them, which enabled Christian universities to adapt to the political transformations of the Republic of China era. Taking Jinling University as a case study, this paper examines how the religious education sector perceived and adapted to the Party-oriented education policy, as well as the process of its acceptance. This analysis offers fresh insights into the transformation of Christian universities during this period.